Forum: The Cantos and PedagogyThe Cantos and Pedagogy. Issue 3 (November 2017) - Kindellan, Michael; Kotin, Joshua
Abstract : The argument of Kindellan and Kotin's essay, ' The Cantos and Pedagogy', is that, contrary to the prevailing critical view, The Cantos is not a pedagogical poem. More specifically, they argue that the poem rejects the idea that a methodological approach to knowledge is desirable. The Cantos is obsessed with who we are, not what we can learn. Put otherwise, the horizon of Pound's concern in The Cantos is ontological, not epistemological. Charles Altieri, Alan Golding, Marjorie Perloff, and Steven G. Yao and Michael Coyle challenge this claim. The range of their replies demonstrates the breadth of the problem at hand. They all construe The Cantos as embodying an alternative pedagogy rather than, as Kindellan and Kotin argue, an alternative to pedagogy.